Bagaimana Aku Jika Tak Ada Gadget: Efektifitas Digital Detox terhadap Happiness - Kharisma Safitri; Muhammad Fajar Yuwanda; Nuzul Khaira (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to examine the effectiveness of digital detox in improving happiness among Generation Z students. An quasi experimental with pretest-posttest control group design. Subjects were psychology students from Padang State University, class of 2021. The results showed that the average gain scores for the experimental (27.6%) and control (7.1%) groups were below the effectiveness threshold (<40%) as defined by Hake (1999), indicating that digital detox was ineffective in enhancing happiness.